The relationship between personal and professional goals and emotional state in academia: a study on unethical use of artificial intelligence - Dolunay, Ayhan; Temel, Ahmet C. (Frontiers in Psychology, 2024)
Artificial Intelligence (AI) is a concept that has been a subfield of computer science since the 1950s.In recent years, with its growing development power, AI technologies have made significant progress and are now being used in many fields. Like in all areas, the use of AI technologies in academia has provided convenience to academics while also bringing ethical debates..The aim is to discuss the views of academics in order to determine what types of scientific ethical violations and prevention methods are involved. In this context, the semi-structured interview technique, which is one of the qualitative research methods, was preferred as the method.In the study, in-depth semi-structured interviews were conducted with 4 ethics experts and 4 psychology experts selected through snowball sampling technique.The data obtained through semistructured in-depth interviews will be analysed using content analysis. Within the context of the literature review and interviews: From a positive perspective, AI usage significantly contributes to making studies more practical. However, it can lead to problems such as unfair authorship, devaluation of human authorship, and incorrect data.The connection between academics' professional advancement goals and emotional states becomes prominent in this context. The potential of AI to facilitate progression can lead to unethical use.To prevent such situations, it is recommended to organize training sessions to increase professional awareness, internalize ethics personally, establish ethical committees specific to the field of AI, conduct more effective audits by academic publication and promotion committees, and implement specific regulations for AI.